Transurethral grooving of the prostate in the treatment of patients with benign prostatic hyperplasia. An alternative to transurethral incision - (:unkn) unknown (My University, 1993)
Various alternatives exist for the treatment of bladder outlet obstruction due to benign prostatic hyperplasia (BPH). Incision of the bladder neck and prostate has proved its efficacy in many studies, especially in small prostates. The major drawback of the procedure is inability to obtain tissue specimens to exclude malignancy. We introduced a method to overcome this drawback by incising grooves at 5 and 7 o'clock with standard resection loops which created not only the incisions but also provided enough tissue for pathological examination. Twenty-five patients with BPH underwent transurethral grooving. Pre- and post-operative urodynamic studies revealed significant improvement in both maximum and average flow rates. The re-operation rate in the entire group was 12%. Transitional cell carcinoma of the prostatic urethra was detected in 1 patient, which proved its superiority to standard incision procedures.
Keywords: Humans; Middle Aged; Postoperative Complications; Aged; Male; Biopsy; Prostatic Neoplasms; Methods; Prostate; Prostatic Hyperplasia; Urethra; Urinary Bladder Neck Obstruction